Novel non-coding transcripts at imprinted loci in mammalian oocytes and embryos - Nenin, Nina (Jihočeská univerzita, 2020)
Aims of this thesis were to annotate novel transcripts within clusters of imprinted genes in mouse oocytes and embryo, to analyze expression changes of these transcripts during mouse embryonic development, to identify enriched sequence motifs and potential transcription factors binding sites at promoters of transcripts within imprinted gene clusters as well as transposable elements acting as promoters of these transcripts and to identify potential candidates for further functional studies, using bioinformatic methods.
Novel non-coding transcripts at imprinted loci in mammalian oocytes and embryos
Keywords: genetics; bioinformatics; imprinting in mammals; novel trananscripts; expression analysis; imprinted genes; mouse transcriptome; transcription factors; regulation of imprinting; transposable elements; genetics; bioinformatics; imprinting in mammals; novel trananscripts; expression analysis; imprinted genes; mouse transcriptome; transcription factors; regulation of imprinting; transposable elements